INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS) AND THEIR ROLE IN IMPROVING THE QUALITY OF THE CONTENT OF FINANCIAL REPORTS COMPARATIVE ANALYTICAL RESEARCH OF A SAMPLE OF IRAQI AND ARAB COMPANIES LISTED IN THE FINANCIAL MARKET (World Economics and Finance Bulletin, 2024)
The current research aims to show the importance of (IFRS) and its impact on the informational content of financial reports and contribute to decisionmaking, and in order for these decisions to be characterized by economic rationality, this information must be characterized by high quality, as decision support has become the main goal of financial accounting reporting information, and to achieve the goal of the study, five Iraqi industrial companies listed on the Iraq Stock Exchange were selected, which prepare their financial reports according to the unified accounting system, Compared with five Jordanian industrial companies listed on the Amman International Market, their financial reports are prepared according to (IFRS) and for the period from (2015-2019), and the data was analyzed according to liquidity indicators represented by (trading ratio), and profitability indicators, which were represented by (net profit margin ratio), and the study resulted in several conclusions, the most important of which was that the application of (IFRS) affects the improvement of the quality of the informational content of financial reports by adding qualitative characteristics (appropriate and honest representation) to the elements of the financial statements, which reflect In light of the conclusions, a set of recommendations were reached, the most important of which was for Iraqi companies to pay more attention to disclosure, presentation and preparation of financial reports, especially in light of the ambiguity that mars some amounts by creating the appropriate conditions and the ideal real environment for the transition to adoption (IFRS) in the near future